2015
DOI: 10.1021/bm5017496
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructural Morphology of Plasticized Wheat Gluten and Modified Potato Starch Composites: Relationship to Mechanical and Barrier Properties

Abstract: In the present study, we were able to produce composites of wheat gluten (WG) protein and a novel genetically modified potato starch (MPS) with attractive mechanical and gas barrier properties using extrusion. Characterization of the MPS revealed an altered chain length distribution of the amylopectin fraction and slightly increased amylose content compared to wild type potato starch. WG and MPS of different ratios plasticized with either glycerol or glycerol and water were extruded at 110 and 130°C. The nano … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 43 publications
7
33
0
Order By: Relevance
“…As shown in previous studies [5,10,12,31,32,33], the non-modified WG powder showed relatively low amounts of β-sheets, as indicated by a flat shoulder in the amide I region (1620–1625 cm −1 ), while peaks at 1660, 1650 and 1641 cm −1 verified the presence of α-helices, α-helices and random coils, and unordered structures, respectively (Figure 3a). Chemical modification of the WG protein (MWG sample) resulted in a slight decrease in the intensity of peaks in the region 1640–1660 cm −1 , indicating that some of either α-helices, α-helices and random coils, or unordered structures became involved in formation of strong hydrogen bonded β-sheets (Figure 3a).…”
Section: Resultssupporting
confidence: 71%
“…As shown in previous studies [5,10,12,31,32,33], the non-modified WG powder showed relatively low amounts of β-sheets, as indicated by a flat shoulder in the amide I region (1620–1625 cm −1 ), while peaks at 1660, 1650 and 1641 cm −1 verified the presence of α-helices, α-helices and random coils, and unordered structures, respectively (Figure 3a). Chemical modification of the WG protein (MWG sample) resulted in a slight decrease in the intensity of peaks in the region 1640–1660 cm −1 , indicating that some of either α-helices, α-helices and random coils, or unordered structures became involved in formation of strong hydrogen bonded β-sheets (Figure 3a).…”
Section: Resultssupporting
confidence: 71%
“…The peak appeared at 2 θ = 16.86° was found to vanish in the composites (curve 1b–1e) which might be due to crosslinking effect of citric acid with wood, MMA‐ g ‐SG and glycerol. The peak intensity corresponding to cellulose became broad due to high protein concentration in starch gluten blend . The high protein concentration increased the cross‐linking reaction between citric acid and the amine groups of gluten protein and thus decreased the crystallinity .…”
Section: Resultsmentioning
confidence: 99%
“…Besides this, gluten finds it use in the composite due to its good adhesive properties . The use of higher percentage of gluten in the preparation of the composites has some negative effect like decrease in the mechanical properties .…”
Section: Introductionmentioning
confidence: 99%
“…Starch is among the most promising natural polymers because of its renewability, biodegradability, abundance, low cost, film‐forming properties, and ease of modification . Nevertheless, native starch without modification is not suitable for most polymer applications.…”
Section: Introductionmentioning
confidence: 99%